Managing Public Relations in an Emerging Economy: The Case of Mercedes in China - Tan, Justin (Journal of business ethics, 2009)
This case study documents a high-profile incident involving the world-famous auto maker Daimler Benz with its customers in China. On the one hand, angry customers felt victimized by the auto maker’s lack of willingness to take responsibility and its double standard between industrialized markets and emerging economies in dealing with customer complaints; on the other hand, the auto maker also felt frustrated at how this product warranty matter quickly escalated into a public relations nightmare. The case illustrates the complexity of operating in emerging markets where institutional environments are vastly different, and the difficulty of balancing business interests with social responsibility. It also illustrates the urgent needs for emerging markets to develop institutional infrastructure to protect consumer rights, and to offer proper channel for conflict resolution.